Does sexual orientation vary between disabled and non-disabled men? findings from a population-based study of men in Australia. Issue 10 (21st October 2020) - Bollier, Anne-Marie; King, Tania; Austin, S. Bryn; Shakespeare, Tom; Spittal, Matthew; Kavanagh, Anne
Abstract: Some research suggests that disabled people are more likely to be sexual minorities than non-disabled people, but this evidence comes mainly from younger or older populations. We used data from a large survey of Australian men aged 18–55 to examine the relationship between disability and minority sexual orientations. Results from our statistical analyses suggest that a larger proportion of disabled than non-disabled men are sexual minorities. Our estimates showed that disabled men were at least twice as likely as non-disabled men to be attracted to females and males, not experience sexual attraction, identify as bisexual, identify as homosexual and have female and male sexual partners—relative to the likelihood of female-only attraction, heterosexual identity and female-only sexual partners. Findings provide new information about sexual diversity in disabled versus non-disabled Australian men, which can help inform inclusive service provision and identify avenues for future research about sexual minority disabled people.